Morphological and functional characteristics of the muscle-tendon unit - Yasuo Kawakami (Japanese Society of Physical Fitness and Sports Medicine, 2012)
The biomechanical features of skeletal muscles are reviewed, with regard to their form and function and anatomical components (fascicles and tendinous tissues). 1) Studies on fascicle architecture are reviewed, highlighting its importance in the force and velocity potentials of the muscle along with its plasticity and muscle-size dependence. 2) The elastic properties of the muscle-tendon unit are described, pointing out the contribution of tendinous tissues as a spring. Functional consequences of tendon elasticity are summarized with respect to exercise performance under mechanically and neurally controlled joint actions, which lead to energy saving of muscle fibers and enhancing the positive work of the muscle. 3) The task-specificity of the muscle as an actuator or a spring and its position dependence (proximal to distal trend of functional divergence) are mentioned. Literature shows that proximal muscles are architecturally designed for actuation and distal muscles are more suited for a spring function. 4) Unique but strange behavior of tendinous tissues, that is seen in stretch-shortening types of movement, is described, suggesting variable elasticity of tendinous tissues that is modulated by muscle activation. 5) Finally, a need to consider multiple muscle-tendon units as a system is introduced to reasonably understand recent findings that otherwise cannot be accounted for. Collectively, it is suggested that the muscle-tendon unit is not only a simple combination of muscle fiber and tendinous tissues acting as actuator and spring, respectively, but also a unit that acts both anatomically and functionally.